Effects of fusidic acid on staphylococcal keratitis. Issue 2 (February 1989) - Tabbara, K F; Antonios, S; Alvarez, H
Abstract : We treated 20 consecutive patients suffering from staphylococcal keratitis with topical fusidic acid 1% suspension in a carbomer gel. Fifteen (79%) of the isolated Staphylococcus epidermidis strains were resistant to methicillin, but all were sensitive to fusidic acid by in-vitro testing. The keratitis showed evidence of healing in 17 (85%) of the 20 patients. The healing times ranged between 5 and 21 days (mean 10.5 days). In this open clinical trial fusidic acid proved to be a safe and effective antibiotic for the treatment of staphylococcal keratitis.